The THE INFLUENCE OF THE BALANCE EYES FACE ARMS SPEECH TIME (BEFAST) DETECTION METHOD ON THE RISK OF STROKE IN THE ELDERLY (In Suwalan Village, Jenu District) - Maulidina Anggraini, Yuanita; Ryandini, Tiara Putri (jfpublisher, 2025)
Introduction. Stroke is a global health problem in the world because it is the main cause of disability in adults and the second cause of death after heart disease. It is important to detect stroke to prevent the condition from getting worse, but sometimes the elderly often ignore the signs of stroke related to the condition they are experiencing. This study aims to determine the influence of the balance eyes face arms speech time (BEFAST) detection method on the risk of stroke in the elderly in Suwalan Village, Jenu District. Method. The research design used in this research is Quantitative True- experimental using the Post Test Only Control Design research method. The population in this study were elderly people who had actively attended posyandu in the last 3 months, totaling 83 elderly people who were selected using a cluster random sampling technique. There were 21 elderly people at posyandu post 1, 21 elderly people at posyandu post 2 and 28 elderly people at posyandu post 3 as samples. The instrument used in this research is an observation sheet consisting of 6 statements. Results and Analysis The results of the research carried out were analyzed using the Man Whitney test with a significance level of α=<0.05. The result obtained is that the sig value. (2-tailed) of 0.001 is proven to reduce the risk of stroke in the elderly, it can be concluded that the hypothesis is accepted the difference between the results of the risk of stroke in the elderly in Suwalan Village, Jenu District in the experimental and control groups. Discussion. Providing the balance eyes face arms speech time (BEFAST) detection method influences the risk of stroke in the elderly. This is influenced by several factors, namely increasing age and hypertension, because as you get older the risk of having a stroke also increases. Hypertension sufferers are more susceptible to stroke, because hypertension accelerates the occurrence of osteochlorosis which can cause weakness in blood vessel walls so that they become brittle and break easily.